Labour Market and Industrial Relations in Vietnam - Artus, Ingrid; Blien, Uwe; Holland, Judith; Phan, Hong Van (Nomos/Bloomsbury, 2015)
The society and economy of Vietnam is still characterised by a rapid transformation process. There is high economic and political pressure on the actors of this country coming not only from internal developments but also from foreign countries. The book is taking stock of the rapid processes of change in the labour market and the industrial relations of Vietnam. The contributions of Vietnamese and international experts cover the institutional arrangements of the labour market and of the system of industrial relations. They look at consequences for welfare and social inequality and treat the relation between culture and the economy in the country. Further contributions compare Vietnam with other developing country and analyse the relationships between international and Vietnamese labour markets. They also address the question whether Asia is a new focal point of industrial conflicts.